Telomeres as a molecular marker of male infertility. (3rd April 2019) - Boniewska-Bernacka, Ewa; Pańczyszyn, Anna; Cybulska, Natalia
Abstract: In recent years, male infertility has become a growing social problem. Standard diagnostic procedures, based on assessing seminological parameters, are often insufficient to explain the causes of male infertility. Because of this, new markers with better clinical application are being sought. One of the promising markers seems to be an assessment of telomere length of sperm. Sperm telomeres, in contrast to somatic cells, are elongated as men age. The results of some studies suggest that telomere length may be relevant in the case of fertilization and normal embryo development. Literature reports indicate that there is a correlation between telomere length of sperm and abnormal sperm parameters. The measurement of telomere length using the method of quantitative PCR could become a new marker of spermatogenesis, which can be useful for evaluating male reproductive age.